If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 9 = 5(x + -2) Reorder the terms: 9 + x = 5(x + -2) Reorder the terms: 9 + x = 5(-2 + x) 9 + x = (-2 * 5 + x * 5) 9 + x = (-10 + 5x) Solving 9 + x = -10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 9 + x + -5x = -10 + 5x + -5x Combine like terms: x + -5x = -4x 9 + -4x = -10 + 5x + -5x Combine like terms: 5x + -5x = 0 9 + -4x = -10 + 0 9 + -4x = -10 Add '-9' to each side of the equation. 9 + -9 + -4x = -10 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = -10 + -9 -4x = -10 + -9 Combine like terms: -10 + -9 = -19 -4x = -19 Divide each side by '-4'. x = 4.75 Simplifying x = 4.75
| -0.96j=-0.73 | | y^7+2y^3-10y^2=0 | | m^2-6m-26=0 | | 120=2nxm*p | | 8p^2*4p= | | 8-7x-4=-18+4x-11 | | 9-5(u-2)=3(2u-1) | | 8c+8=244 | | 3m=2(4m-5)-10 | | 5y-3x=40 | | 2+4x=-8+25x | | 4x-10=6x-2 | | 0.06x+.05(2-x)=.10(-21) | | 2x+13=3x-2 | | -10r-2r=13+2r | | 3N+43=49 | | 6x-5=5-17 | | 3a-5ifa=6 | | -24x-6x=-7 | | 12X^2+12y^2+12x+8y+8=0 | | 6x+5y=114 | | x+8.9=11.5 | | x^2+4x-316=0 | | 8+4x+6x=-102 | | x^3-3x^2+2x-504=0 | | -3(4+a)=15 | | 10x^2-x^3-16x=8 | | 0.25r-0.125+0.5r=0.5+5 | | 0=9x^3+9x^2-x-1 | | 4-2x=6-3x | | 4x-20=20-5x | | (41)*(-30)= |